Nilai Historis Pada Makanan Tradisional Tiliaya Dalam Konteks Kebudayaan Gorontalo - Irma Kharisma Hatibie (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2019)
Tiliaya is one of Gorontalo traditional food which has historical values in Gorontalo society. Tiliaya is a kind of food that sarved in a tradition ceremony such as wedding, weighting, welcoming government guest and in traditional ceremony of praying for the soul of those who have passed away (doa arwah) and also served in the beginning of fasting month or Ramadhan. However now days not many people know the history of the traditional food that has been bequeathed. History and values of tiliaya that related to Gorontalo tradition and the implication of traditional food to the society social life. The objectives of this article is a first study to explain the history values of a traditional food that has been being an identity of a region, in the society cultural context of Gorontalo. Method that used in this article is descriptive qualitative by collecting the relevant literature. The respondent that has been interviewed in this article is the original society of Gorontalo, that has been choosen randomly but know the history of tiliaya and also the tradition of Gorontalo. This article conclude that tiliaya is a food that describes Gorontalo tradition and culture. Tiliaya has a historical values that almost forgotten, so this must be preserved. The existing of tiliaya shows the past society way of life and the present society who still preserves traditional food as part of tradition and local wisdom.